'Fluvial geomorphology and environmental design': Restitution for damage, rehabilitation, restoration or rewilding?. Issue 2 (3rd November 2021) - Newson, Malcolm
Abstract: Gregory's pioneering work on progressive river channel change, driven in England by both natural and anthropogenic forces, helped to guide major concepts and roles for fluvial geomorphology. It opened the door to a steep rise of applied fluvial geomorphology and a bigger role in public policy and river basin management. The channel change paradigm spans the millennia; by the late 20th century, the extent of Anthropocene harm to rivers justified both a radical label as 'damage' and a professional focus to prescribe remedies. Imitating engineering, then dominant in river management, Gregory favoured the term 'design'. The damage principally impacted river habitat and increasing collaboration with freshwater ecologists in the restitution of damage became part of the international move to 'river science'. European legislation strengthened the legal status of physical habitat in overall river quality. In the 21st century fluvial geomorphology has both strengthened and diversified further within 'river science', but also gaining social, behavioural, even political, insights through 'citizen science' and the 'co‐design' of river corridor projects with communities. The professional challenges of the climate and biodiversity emergencies return us to Gregory's question, 'how applied should we become?' The increasingly public profiles of, for example, flood risk policy require river scientists to participate in recommending and co‐designing options such as rehabilitation, restoration and rewilding. The separate and joint contributions of these options are discussed through the geomorphological prism. Progressive and episodic channel changes will increase as the drivers and remedies interact; we must play a role in scenario setting and adaptive management, promoting workable collaboration between natural and social sciences, especially in the contested field of design. Abstract : Gregory's influential work on river channel change is placed on a timeline in which fluvial geomorphology has joined river science and become professionally recognized in environmental design. River science now has a citizen science dimension and works with catchment and riparian stakeholders. Restoration of anthropogenic damage is a major future role, playing a part in addressing climate and biodiversity crises.